Restoration thinning reduces bush encroachment on freehold farmlands in north-central Namibia. (27th March 2021) - Nghikembua, Matti T; Marker, Laurie L; Brewer, Bruce; Leinonen, Arvo; Mehtätalo, Lauri; Appiah, Mark; Pappinen, Ari
Abstract: Bush encroachment affects ~45 million ha of Namibia and, without appropriate restoration measures, it negatively affects rangeland productivity and biodiversity. Thinning is a common method to counteract bush encroachment. The thinning strategy applied in north-central Namibia was assessed to examine how effective it has been in reducing bush encroachment. Trees/shrubs were selectively thinned manually, targeting all height classes, except individuals with stem diameters ≥18 cm. We investigated the effects on the vegetation and soil properties using surveys on three freehold farms (in 2016 and 2017) in bush-encroached and previously thinned habitats. Our results revealed significant differences in the mean total nitrogen (TN) content between the treatments; thinned areas had higher TN content which would be beneficial for fast-growing grasses. In the thinned plots, the occurrence probability of red umbrella thorn ( Vachellia reficiens Warwa) was significantly reduced, indicating that it was the most harvested species; and umbrella thorn ( Vachellia tortilis (Burch.) Brenan spp. heteracantha ) was increased, indicating that it favoured reduced densities of dominant species. Natural regeneration was rapid; the tree/shrub abundance in the 0–1-m height class in the thinned area surpassed those in the non-thinned by 34 per cent, ~7.2 years since thinning. Thinning significantly reduced tree/shrub abundances of the 1–3- and >3-m height classes, which was still evident 7.2 years since thinning. Based upon the generalized linear mixed-effects model, tree/shrub counts between treatments may equalize in ~14 and 15 years for the 1–3- and >3-m height classes, respectively. Thinning was effective in reducing tree/shrub abundances and can be used to restore wildlife habitat on the Namibian farmland: however, post-thinning management is required to maintain an open savannah vegetation structure as the 0–1-m height class cohort will eventually grow into mature trees/shrubs.